Penerapan Self Asessment System Bea Perolehan Hak atas Tanah Bangunan dalam Transaksi Jual Beli - Rahayu Harina; Busyra Azheri; Yussy Adelina Mannas (Media of Law and Sharia, 2023)
According to Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments, it is stated that the BPHTB collection is calculated and paid by the taxpayer himself, in the sense that the BPHTB adheres to a self-assessment system collection system. The essential imposition of BPHTB based on the Regional Regulation of Agam Agency Number 7 of 2011 concerning Regional Tax states that the basis for the imposition of BPHTB for a sale and purchase transaction of land or buildings is the transaction value, which is the transaction value here according to the elucidation of Law Number 20 of 2000 concerning Acquisition Fees. The values that occur and are agreed upon by the parties involved are land and building rights. However, in reality, BEKEUDA in Agam Regency is more dominant in using market prices. This study aims to analyze and answer questions from the formulation of the problem, namely how is the application of the principles of the self-assessment system at BPHTB in buying and selling transactions of land and/or buildings in Agam Regency, what is the basis for determining the sale and purchase price of land and/or buildings at BPHTB by BAKEUDA of Agam Regency, what is the legal certainty regarding the determination of the sale and purchase price set by BAKEUDA of Agam Regency. The approach method in this study is empirical-juridical, and the specifications used in this study are analytical-descriptive. Based on the research results, it can be concluded that, the application of the principle of a self-assessment system is not purely following the mandate of the law. The considerations that determine the value of the buying and selling price by BAKEUDA are the results of previous verification, the opinion of the nagari guardian, the opinion of the community shop, and the price on the marketplace on social media. The legal certainty regarding the determination of the sale and purchase price is not yet strong and certain.